Exploring the Potential of Recyclable Steel in Circular Economies - Deepti Pande Rana; Kanishka Singh (International Journal of Manufacturing and Production Engineering, 2024)
As the global community faces the pressing challenges of environmental degradation and resource depletion, the imperative for sustainable solutions has never been more pronounced. This research introduces an in-depth exploration into the realm of recyclable materials, with a specific emphasis on steel—an essential component in various industries and a major contributor to environmental impact. The research investigates current recycling technologies and processes that facilitate the transformation of steel into a circular resource. Additionally, it explores the economic feasibility and scalability of implementing these recycling methods on a broader scale. Special attention is given to the advancements in technology that enhance the efficiency of steel recycling and the integration of circular economy principles. The research examines the role of stakeholders, including government bodies, industries, and consumers, in promoting the adoption of recyclable materials, specifically steel. It addresses the challenges and opportunities associated with fostering a sustainable mindset and creating a more circular economy.
Keywords: Broader scale; Exploration into the realm of recyclable materials; Fostering; Recyclable material; Role of stake holder; and scalability; feasibility